Hydrochemical Assessment of Water Quality at the Uzunbulok Water Treatment Facility - Abjalov, Alimardon; Eshmurodova, Nargiza; Abdullayeva, Mubarak (American Journal of Biology and Natural Sciences, 2026)
This study presents an integrated assessment of water quality at different treatment stages of the Uzunbulok Water Treatment Facility, with particular emphasis on effluent quality and compliance with drinking water standards. Hydrochemical and biological indicators were analyzed to evaluate the efficiency of sedimentation and mechanical (sand) filtration processes. Water samples were collected at the influent, settling tank, filtration stage, and final effluent, and key physicochemical parameters were measured in accordance with national and international guidelines. The results indicate a consistent improvement in water quality throughout the treatment process. At the effluent stage, concentrations of nitrates (2.0 mg/dm³), nitrites, and ammonia were well below permissible limits, while heavy metals such as iron and zinc were within acceptable levels or not detected. Parameters including pH, turbidity, odor, taste, and transparency met recommended standards. Overall, the Uzunbulok Water Treatment Facility effectively provides safe drinking water and demonstrates reliable treatment performance.